Prediksi Kebangkrutan Menggunakan Metode Altman Z-Score Modifikasi pada PT Inti (Persero) - Selly Tania; Leni Nur Pratiwi; Banter Laksana (Indonesian Journal of Economics and Management, 2021)
This research aims to find out the financial development and prediction of bankruptcy from PT INTI (Persero) in 2015 - 2019. Descriptive method with a quantitative approach was used in the research. The object of the research is the annual financial statements of PT INTI (Persero) in 2015 - 2019. Data analysis tools uses Microsoft Excel with Altman Z-Score Modification model formula that uses 4 financial ratios that are Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Taxes to Total Assets, and Book Value of Equity to Total Liabilities. The calculation results will show the company's categories include safe, grey area, and distress. The results showed financial aspects of the company decreased and Z-Score in PT INTI (Persero) in 2015 - 2019 was in the potential for bankruptcy for the past 5 years.